2019
DOI: 10.1371/journal.pone.0217931
|View full text |Cite
|
Sign up to set email alerts
|

Perceived publication pressure in Amsterdam: Survey of all disciplinary fields and academic ranks

Abstract: Publications determine to a large extent the possibility to stay in academia (“publish or perish”). While some pressure to publish may incentivise high quality research, too much publication pressure is likely to have detrimental effects on both the scientific enterprise and on individual researchers. Our research question was: What is the level of perceived publication pressure in the four academic institutions in Amsterdam and does the pressure to publish differ between academic ranks and disciplinary fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 43 publications
(49 reference statements)
5
54
8
1
Order By: Relevance
“…The survey consisted of three parts, one of which was the list of 60 research misbehaviours described here. The remainder comprised two instruments, one about the research climate for integrity [17] and another about the degree of perceived publication pressure [18]. The data described here extend our previous findings [17] by identifying the research misbehaviours that are perceived to impact the research climate most.…”
Section: Quantitative Data Collection Proceduressupporting
confidence: 52%
“…The survey consisted of three parts, one of which was the list of 60 research misbehaviours described here. The remainder comprised two instruments, one about the research climate for integrity [17] and another about the degree of perceived publication pressure [18]. The data described here extend our previous findings [17] by identifying the research misbehaviours that are perceived to impact the research climate most.…”
Section: Quantitative Data Collection Proceduressupporting
confidence: 52%
“…The publication pressure is perceived to be the highest among assistant and associate professors. This accords well with a study by Haven et al (2019) who focus on different disciplines at four academic institutions in Amsterdam. These are indeed the crucial periods in an academic career when tenure and promotion depend to a large extent on one's publication record.…”
Section: Measuring and Explaining The Work Pressuresupporting
confidence: 90%
“…We understand publication pressure, or pressure to collect points (Haven et al, 2019a(Haven et al, , 2019b, or "pointing pressure" in Poland, as:…”
Section: Publication Pressure and Misconduct In Researchmentioning
confidence: 99%
“…In a study by Tijdink et al (2014), 72% biomedical scientists rated publication pressure as "too high", and 61% reported that they agreed with the following statement: "Publication pressure leads to serious worldwide doubts about the validity of research results". Strong publication pressure across academic ranks and disciplinary fields has been associated with a negative attitude toward the current publication climate (Haven et al, 2019a(Haven et al, , 2019b, researcher burn-out, and cynicism in published research (Tijdink et al, 2013) and has negatively affected the quality of research and the researchers themselves (Rawat and Meena, 2014;van Wesel, 2016). However, other research (Fanelli et al, 2015(Fanelli et al, , 2017 suggest a lack of clear association between pressure to publish and scientific integrity, which indicates the need for further studies in this area.…”
Section: Publication Pressure and Misconduct In Researchmentioning
confidence: 99%